Risk evaluation of failures of the running gear with effects on rail infrastructure. (October 2021) - Poveda-Reyes, Sara; Rizzetto, Luca; Triti, Chiara; Shi, Dachuan; García-Jiménez, Elena; Molero, Gemma D.; Santarremigia, Francisco E.
Graphical abstract: Highlights: Defects on rolling stock components have consequences on the infrastructure. FMECA was used for the evaluation of the criticality of running gear assets. Wheelset and bogie frame failures have a very critical effect on infrastructure. Components with high criticality are the traction rod and the bogie centring plate. Monitoring systems should include camera systems, sensors and modelling algorithms. Abstract: Preventive and corrective maintenance of the different components of rolling stock is mandatory to guarantee the safety of passengers and workers when using rail transport. Although different studies and models of degradation have been developed, the actual effect of rolling stock component defects in the infrastructure is not totally clear. From the different components of rolling stock, failures of elements of the running gear are more likely to cause track deterioration due to more severe wear wheel-rail interactions, producing undesirable effects on the infrastructure that can end in derailments. The aim of this paper is both to analyse through a failure modes and criticality analysis (FMECA) the different failure modes of the running gear and their effect on rail infrastructure and to analyse the prioritisation based on their criticality in order to give some insights into which components should receive special attention in maintenance procedures. Failures based on maintenance registers of passenger vehicles of railway companies involved in the Assets4Rail project were analysed. Results showed that defects related to wheels such as cracks, the movement of the wheel in the axle seat, failure of the axlebox bearing, or damage of the bogie frame are some of the failures with more severe consequences.